Educação inclusiva : desafios e expectativas na atuação de psicólogos e psicólogas no Estado de Mato Grosso - Carvalho, Gessika Brasileira Macedo de (2019)
The present study is the result of a research carried out with Psychology professionals who work in the educational area, within an inclusive educational proposal, specifically, with students with disabilities. It presents current research on Psychology and inclusive education and allows a discussion about the performance of psychologists and psychologists in these spaces. In this way, it aims to understand the practices of psychologists and psychologists in inclusive education based on their expectations and real possibilities of acting, to understand the initial expectations of each participating professional, to present what actions are carried out in the work environment, to point out their main difficulties, and their conceptions about the process of inclusion of children with disabilities, and how their work turns to this public. It is a qualitative research involving seven professionals who work in the educational area in different municipalities of the state of Mato Grosso. The procedures used for data production were the focus group and individual semi-structured interviews. The data were analyzed in the light of historical cultural psychology and the technique used was Thematic Analysis, through the creation of groups of answers, according to the categories of the triggering questions. From a general analysis of the data, we defined significant units that were discussed considering the issues currently studied regarding inclusive education in relation to the ideal of performance, the difficulties existing in professional practice and other aspects considered relevant to the theme. The results show that psychology professionals work with educational agents, through training courses, as well as with students and their families, seeking to establish a dialogue with both the institution and the community. Aspects related to their difficulties also stand out such as the insecurity and lack of training of psychology professionals in the educational area. Regarding their expectations, the participants present in their speeches the need for changes regarding the performance of other educational agents in relation to the inclusion of persons with disabilities, also highlights the search for developing a practice more focused on school issues, training of professionals, in order to contribute to the development of a broadly inclusive education that considers the capacity of all students, including those with disabilities, and emphasizes the importance of psychologists and psychologists in this process.